Visual Representations of Acoustic Data: A Survey and Suggestions. Issue 4 (2nd October 2017) - Walker, Gareth
ABSTRACT: Visual representations of acoustic data are becoming more common in Conversation Analysis (CA) and Interactional Linguistics (IL) research. This article provides a survey of visual representations of acoustic data in the journal Research on Language and Social Interaction . Shortcomings in their preparation and use are identified and discussed. Comparisons are made with visual representations prepared by expert phoneticians. Suggestions are made as to how visual representations could be prepared and used more effectively to support CA/IL researchers' claims and to allow readers to independently verify them.